Trends in management of ocular syphilis in tertiary uveitis centre in Prague, Czech Republic - Klimova, Aneta; Brichova, Michaela; Heissigerova, Jarmila; Rihova, Eva; Svozilkova, Petra (Biomedical papers, 2023)
Aims. To analyse the hallmarks of ocular manifestations of and therapeutic modalities for syphilis in the last two decades. The clinical features of syphilitic uveitis, and association with the human immunodeficiency virus (HIV) coinfection are described. Methods. Retrospective study of 16 patients diagnosed with ocular syphilis confirmed by serological tests in the General University Hospital in Prague between the years 2004 and 2021. General characteristics of ocular and systemic manifestations and visual functions were analysed. Results. An increasing incidence of syphilitic uveitis correlates with a general rise in syphilis cases. In our study, the ocular manifestation of syphilis was panuveitis (44%), posterior uveitis (31%) and anterior uveitis (25%). Posterior uveitis was found in 3 patients (19%) associated with preretinal infiltrates, that are often present in syphilitic uveitis. The worst visual outcomes were among patients with human immunodeficiency virus (HIV) coinfection and/or neurosyphilis, however the data were not significant. Optic disc edema was present in 56%, macular involvement in 37% of patients. Overall, 31% of patients in our cohort had persistent visual field defects due to impairment of their optic nerve or macula despite the final median Snellen visual acuity of 1.0. Two out of sixteen patients were treated with corticosteroids in addition to antibiotics. Conclusion. Posterior uveitis with preretinal infiltrates and optic disc edema should arouse suspicion of ocular syphilis. Recent data show the advantages of adjacent systemic corticosteroid treatment for severe forms of syphilitic uveitis and/or neuritis. Our observation supports this finding.
Keywords: syphilis; uveitis; corticosteroids; optic neuritis; optic disc edema